Jima' Husband's Ethics Toward the Wife According to Hadith Demands - Suryani Suryani (IAIN Bengkulu, 2022)
This research aims to describe the ethics of a husband in having sex with his wife, as a reference for the relationship between husband and wife in the household. Therefore, the problem in this research is what the etiquette of a husband is when having sexual intercourse with his wife, and what prohibitions are made when having sexual intercourse with his wife. This type of research is library research with data sourced from literature, both hadith books and books and articles related to this research. The research analysis is descriptive analysis to find the law and ethics of having sex with one's wife from Hadith guidance. Research shows that in the hadith it is forbidden to have sexual intercourse with one's wife from the anus and it is haram, Allah has cursed this act. There are several ethics in having sex with your wife, namely with my love, you can't force it, you can't be rude, you can't make it difficult.